Study guides

Q: What is the answer to 5 plus 5 plus 5 - 5 plus 5 plus 5 - 5 plus 5 x 0?

Write your answer...

Submit

Related questions

(5+5) + (5-5) + (5 + 5 - 5) + (5 x 0) = 10 + 0 + 5 + 0 = 15

x2+6x+5=0(x+1)(x+5)=0x=-1 and x=-51-6+5=0 and 25-30+5=0 so both answers work.

x = -1/2 or -5 2x2 + 11x + 5 = 0 ⇒ (2x + 1)(x + 5) = 0 ⇒ (2x + 1) = 0 → x = -1/2 or (x + 5) = 0 → x = -5

-5

x=0

x2 - 10x + 25 = 0(x - 5)(x - 5) = 0x - 5 = 0x = 5

x2 + 9x + 20 = 0 ∴(x + 4)(x + 5) = 0 ∴x ∈ {-5, -4}

X = 5

x2 + 14x + 45 = 0 => x2 + 9x + 5x + 45 = 0 => x(x + 9) + 5(x + 9) = 0 (x + 9)(x + 5) = 0 so that x = -5 or x = -9

x+4x+5 = 0 5x + 5 = 0 5x = -5 x = -1

x2 + 11x + 30 = 0 (x + 5)(x + 6) = 0 so the roots are -5 and -6

(x+4)(x+5) = 0 x = -4 v x= -5 However this can also be an answer: (x+4)(x+5) = 0 x2 + 9x + 20 = 0

Factors are (x + 5)(x + 1) so x = -5 or -1

0

X should be zeroas:X + 5 = 2X + 5so, 2X - X = 0 or X = 0

12x^3+17x^2+5x=0x(12x^2+17x+5)=0x(x+1)(12x+5)=0x=0x=-1x=-5/12

(5, 0)

the answer is x = 0

This is relatively easy to solve, only requires application of the laws of indices. (x+5)1/5 - (x+5)6/5 = 0 => (x+5)1/5 - (x+5)(x+5)1/5 = 0 => (x+5)1/5 (1 - (x+5)) = 0 => -(x+5)1/5 (x+4)=0 since the expression equals 0 one term or the other has to be 0 therefore x= -4 or x= -5

4

x = -5/3

-(x - 5)(x - 5) or -(x - 5)2

(x-3)(x-5) = 0

you would first do 10+5x-5=0, then 5x+5=0 and is factored by 5(x+1)=0. or if you want to know what x equals with, x=-1

The domain is the real numbers except {0, 5}.